Comparison of trans-umbilical single-port laparoscopic complete extraperitoneal closure and laparoscopic intracorporeal closure for pediatric inguinal hernia: a randomized controlled study - Li, Yanyi; Jin, Zhu; Tang, Chengyan; Gong, Yuan; Huang, Lu; Du, Qing; Xia, Xinrong; Zhu, Daiwei; Zhou, Wankang; Li, Zeping; Wang, Weiao; Liu, Yuanmei; et al. (Frontiers in Pediatrics, 2024)
BackgroundThe purpose of this study was to compare the outcomes of Trans-umbilical single-port laparoscopic complete extraperitoneal closure (LCEC) and laparoscopic intracorporeal closure (LIC) for inguinal hernia by analysis of follow-up data over 5 years.MethodsIn this prospective randomized controlled trial, 524 children with inguinal hernia were randomly assigned to undergo LCEC or LIC between August 2016 and December 2017. The primary outcome measures were the success and recurrence rates. The secondary outcome measures were operative time; length of hospital stay; postoperative pain score; and incidence of postoperative complications, including rates of wound infection, stitch abscess, and testicular atrophy.ResultsPrimary analysis of the 227 patients in the LIC group and 215 patients in the LCEC group revealed that in the LCEC group, the success rate of was significantly higher in LCEC group (96.7% vs. 90.3%, P < .05) and the length of hospital stay was significantly shorter (P < .05) than those of the LIC group. Neither the recurrence rate (P > .05) nor the operative time (P > .05) of the groups significantly differed. The pain scores at postoperative 12 and 24 h were significantly lower in the LCEC group than in the LIC group (P < .05). The incidence rates of wound infection (0.93% vs. 5.7%, P < .05) and stitch abscess (1.4% vs. 7.0%, P < .05) were significantly lower in the LCEC group than in the LIC group. No testicular atrophy occurred in either group.ConclusionLCEC is associated with better clinical success and fewer postoperative complications for repair of pediatric inguinal hernia compared with LIC.